2015
DOI: 10.14237/ebl.6.1.2015.294
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Non-Targeted LC-MS Approach for Identifying Ancient Proteins: Method Development on Bone to Improve Artifact Residue Analysis

Abstract: Identification of protein residues from prehistoric cooking pottery using mass spectrometry is challenging because proteins are removed from original tissues, are degraded from cooking, may be poorly preserved due to diagenesis, and occur in a palimpsest of exogenous soil proteins. In contrast, bone proteins are abundant and well preserved. This research is part of a larger method-development project for innovation and improvement of liquid chromatography – mass spectrometry analysis of protein residues from c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 43 publications
(63 reference statements)
0
4
0
Order By: Relevance
“…The TME mainly consists of the tumor stroma, adjacent tissue cells, microvessels, immune cells, and immune molecules. 415 CSCs not only adapt to changes in the TME but also affect the TME. Concurrently, the microenvironment also promotes the self-renewal of CSCs, induces angiogenesis, recruits immune and stromal cells, and promotes tumor invasion and metastasis (Fig.…”
Section: Major Signaling Pathways In Cscsmentioning
confidence: 99%
“…The TME mainly consists of the tumor stroma, adjacent tissue cells, microvessels, immune cells, and immune molecules. 415 CSCs not only adapt to changes in the TME but also affect the TME. Concurrently, the microenvironment also promotes the self-renewal of CSCs, induces angiogenesis, recruits immune and stromal cells, and promotes tumor invasion and metastasis (Fig.…”
Section: Major Signaling Pathways In Cscsmentioning
confidence: 99%
“…Plasma proteins and blood clotting proteins are also typically present in bone and dentine proteomes, including prothrombin (F2), coagulation factor IX (F9), and coagulation factor X (F10). To date, ancient bone proteomes have been studied in humans, ,,,, mammoths, , moas, cattle, , horses, , turkeys, rabbits, squirrels, extinct rhinoceros, and ancient dentine proteomes have been studied in humans ,, and extinct rhinoceros …”
Section: Applications In Paleoproteomicsmentioning
confidence: 99%
“…Immunoprecipitation methodology could also increase confidence in the use of antibodies for direct analysis of fossil soft tissues because it can remove the concerns of nonspecific binding by validating the antibody target . Because mass spectrometry provides direct identification of isolated/enriched proteins, it is possible to directly evaluate the specificity of the antibodies/aptamers and rule out cross-reactivity with humics or other diagenetic molecules as the source of immunological response . Further, we have found that some low-abundance bone proteins (e.g., hemoglobin) solubilize better in extraction buffers that are nonoptimal for general proteome, suggesting that extraction reagents may themselves be optimized for more targeted investigations.…”
Section: Future Directions In Dtppmentioning
confidence: 99%